SELF-DEFENSE IN NICHOLAS SPARKS’ THE LAST SONG (CHARACTER ANALYSIS) - Nadia Adelia Baadib; Mister Gidion Maru; Ceisy Nita Wuntu (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2022)
To reveals the self-defense of Ronnie Miller in Nicholas Sparks The Last Song. In this research the writer used qualitative method in analyzing the novel. It means that, this research does not deal with numbers or diagrams as in quantitative research. This research uses the theory of Sigmund Freud's Psychoanalysis. which states that psychics is a literary theory that examines the psychological elements of the characters in literature. the researcher concludes that there are threemain characters of self-defense reflected from Ronnie Miller as a daughter in her family and major character in this novel. Those are: Have a sense of Concern over hatred, recover quickly from difficulties and toughness and have a strong determination, Self-defense is an act of defend ourselves from obstacles, challenges and problems and take those parts as self-improvement, related with the novel it is against the negative impact waftre her parents divorced. Finally, the researcher concludes that Ronnnie MillerThe Last Song as a broken home child could be faced by self-defense and inner powerto survive from her condition eventough sometimes she faced many problems which is impact from her family condition.